The Effects of Colours on Preschoolers’ Behaviour: An analysis of Colour-Mood Association on Preschoolers Aged 4 to 6 - Lai Imm, Jenny Lee; Bahauddin, Azizi (2008)

(untitled)
Typically set up learning environments for preschoolers often end up, with just an interior that is only furnished with posters on walls, paste-up decorations, toys, and a typical furniture layout.